Hubungan Karakteristik Dokter Dengan Kelengkapan Catatan Laporan Operasi Di RSU Queen Latifa Yogyakarta Tahun 2016 - Yulida, Rina, Ibnu Mardioko, SKM.,MM, Sri Darnoto, SKM, MPH (2016)
Medical records were good and should the quality indicatos of the completeness, accuracy, timely and have the legal aspects. Objectives Knowing Relationship Characteristics of doctors by Gender, Age and Lenght of working Work with Reports Completeness of Operations In RSU Queen Latifa. This research method using observational analytic design with cross sectional approach. The study population was all file statements of operations in 2015. The samples was 166 medical record file by using purposive sampling method. Statistic test using Chi Square (X2). The results is there is a relationship between characteristics doctor by Gender (p-value 0.02) age (p value 0.02) and length of working (p value 0.00) with the completeness of operation report. There is a relationship between the characteristics of doctor with a complete statements of operations with a value of p (0.00). The count of complete report operations by doctor who have characteristics female, aged 25-45 years old and > length of working 3 years more than doctors who have characteristics male, aged 46-65 years old and length of working 1-3 years Keywords: Characteristics of Doctors, Completeness, Operation report